Poverty and volunteers. Critical analysis of the discourse applied to three social programmes in the city of Valparaíso - Vera, Daniel (Última Década, 2020)
The article presents a study over the discourses on poverty produced by young volunteers that work in three different social programmes of the City of Valparaíso. The research work was of a qualitatitive discursive kind and text analysis were carried out as well as individual and group semi structured interviews. A total of three technicians responsible of each programme and 24 young people took part in the study. The results showed a discursive order noted by presenting three poverty variations: a) individual clue, b) structural clue and, c) existential clue. In a social-institutional order distinguished by a social life merchantilizing process, state sphere loss of influence, surging of the relational sphere and high assent in the poverty social intervention, the first discursive variety appears as the one with higher authorization and legitimacy, the second appears to be in a de-authorization process and the third one is rather invisible, although not loosing circualtion legitimacy.